Mobile Pastoralism as a retro-innovation for a sustainable future - Yilmaz E. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Mobile pastoralists the world over share a common understanding of the rangelands they live in and a common ability to read these landscapes and be part of it. There is a strong linkage between the maintenance of mobile pastoralism and the protection of rangeland ecosystems. Yet they are also facing unprecedented challenges and the very same pressures that threaten rangelands also threaten their itinerant ways of life. However the voice of the mobile pastoralist is little heard in the cacophony of modern existence and general discord with the natural world. This manuscript, considering the many benefits of mobile pastoralism for rangeland ecosystems, raises suggestions for reflection towards ensuring the needed shift for conservation of mobile pastoralism and rangelands and promotes the International Year of Rangelands and Pastoralists (IYRP) initiative as a global opportunity to increase knowledge and understanding and to develop sustainable actions for conserving these ecosystems and the pastoralists who rely on them.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)